Exploring the role of volume energy density in altering microstructure and corrosion behavior of nitinol alloys produced by laser powder bed fusion - Gopinath Perumal; Karthikeyan Tamil Selvam; Mark Swayne; Eanna McCarthy; Abhishek Babu; Dmitry Dzhurinskiy; Dermot Brabazon (Scientific Reports)
Abstract In the realm of materials science and engineering, the pursuit of advanced materials with tailored properties has been a driving goal behind technological progress. Scientific interest in laser powder bed fusion (L-PBF) fabricated NiTi alloy has in recent times seen an upsurge of activity. In this study, we investigate the impact of varying volume energy density (VED) during L-PBF on the microstructure and corrosion behaviour of NiTi alloys in both scan (XY) and built (XZ) planes. The microstructural evolution in both planes was characterized by electron backscatter diffraction and phase change temperatures were characterized using differential scanning calorimeter measurements. Electrochemical experiments were carried out to compare the specimens produced at high laser energy density and low laser energy density. The results indicate that employing high laser energy density in the production of NiTi alloy induces discontinuous dynamic recrystallization, contributing to grain refinement. This in turn enhances the corrosion resistance of the specimen. X-ray photoelectron spectroscopy was employed to examine the type of oxide layer that developed on the samples. The increased resistance to corrosion in a high laser energy density sample can be associated with the formation of a stable and homogeneous passive layer with enriched TiO2 as opposed to Ti2O3. This exploration has unravelled the intricate relationship between VED, the microstructure, and the corrosion properties of L-PBF fabricated NiTi alloys, offering valuable insights into their performance for diverse applications.